Non-Instrumental Pulp Therapy for Deciduous Molars: A Global Bibliometric Analysis of Clinical Studies - Rayza Verônica Soares Carvalho; Marina de Deus Moura de Lima; Cacilda Castelo Branco Lima; Marcoeli Silva de Moura; Caroline Barros Oliveira; Lucia de Fátima Almeida de Deus Moura (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate the bibliometric characteristics of clinical studies about the non-instrumental technique with antibiotic paste. Material and Methods: The Web of Science database 'Core-Collection' was searched by two researchers. The following bibliometric parameters were examined: number of citations, authorship, institution, country, journal title and impact factor, study design, year of publication, and keywords. Scopus and Google Scholar databases were used to compare the number of article citations. The VoSviewer software was used to generate collaboration networks. Results: 452 articles were recovered with the search key, and 18 articles were included. The number of citations ranged from 0 to 80, and the number of authors ranged from 2 to 7. Japan had the highest number of citations (n=80). Clinical trials were the most common study design (n= 6). The journals that published the most articles were Pediatric Dentistry (22.2%), Journal of Clinical Pediatric Dentistry (16.6%), Contemporary Clinical Dentistry (11.2%), and International Journal of Pediatric Dentistry (11.2%). Most papers originated from Brazil, the United States of America, and India. Conclusion: The study showed increased publications with a clinical focus in the last decade on the LSTR/NIPT technique, with Brazil leading in the number of relevant publications. It also provided clinicians and researchers with articles on an alternative technique for pulp therapy in deciduous teeth with pulp necrosis.